"Algorithm breakers" are not a different "species": Attitudes towards trade unions of Deliveroo riders in Belgium - Kurt Vandaele; Agnieszka Piasna; Jan Drahokoupil (European Trade Union Institute (ETUI), 2019)
This working paper investigates a rare case of platform work performed in the realm of regulated employment and explores the attitudes of platform workers towards collective representation. The argument is developed that workers' attitudes and their propensity to engage in collective action can be related to their demographic and socio-economic characteristics, and to their experiences of job quality. The empirical analysis is based on a case study of Deliveroo, a place-based food delivery platform. In Belgium, Deliveroo used another labour market intermediary, SMart, to organise, manage and legalise workers' employment status. Thus, effectively, Deliveroo riders worked as dependent employees but were hired by SMart, not Deliveroo. This arrangement was unilaterally terminated by Deliveroo during the period under analysis, sparking discontent and active protests among its riders. The results show that platform workers, in our case predominately young students, are not essentially different to their peers in their views on trade unions and their inclination to unionise. They do not generally hold negative views towards unions, and do not consider unions incompatible with platform work. Instead, the results point to a lack of union activity in reaching out to riders as a reason for their non-membership. Engaging with them may offer trade unions a window of opportunity to win trust and demonstrate the added value of union membership in their school-to-work transitions.
Keywords: 330; atypical employment; union membership; Belgium; Atypische Beschäftigung; Gewerkschaftsmitgliedschaft; Belgien